INDEPENDENT WORK OF INTERNS AT THE DEPARTMENT OF MEDICINE AND THERAPEUTICS FAMILY - Zhdan, V.M.; Kitura, E.M.; Babanina, M.; Volchenko, G.V.; Tkachenko, M. (World of Medicine and Biology, 2016)
The article says about the features of organization self-education of interns in the chair of family medicine and therapy: outpatient care, observetion of patients in the hospital, participation in the preparation of clinical and clinical-anatomical conferences, abstract reviews, multimedia presentations; given the form of distance learning, organization of scientific work of interns.
Keywords: self-education; postgraduation; speciality "General practice - family medicine"